Implementasi Hukum Kebijakan Pemberdayaan Perempuan Miskin Melalui Program Keluarga Harapan (PKH) di DINSOSPERMADES Kabupaten Banyumas - Sabrina Esahstia, Haeza; Musyahadah Rahmah, Alef; Ajeng Tri Utami, Nurani (LPPM Universitas Harapan Bangsa, 2024)
The government, in empowering women from poverty so they can participate and enjoy development, issued the Family Hope Program (PKH) policy. This research aims to examine the implementation of the law and the factors that tend to influence the legal implementation of the policy of empowering poor women through PKH. This research is qualitative research with an empirical juridical approach. The results of the research show that the implementation of the legal policy for empowering poor women through PKH in the Banyumas Regency Dinsospermades has gone well, this can be seen from the good planning, socialization and education about PKH; good PKH assistance; good increase in family capacity; and good PKH evaluation. There are supporting and inhibiting factors that tend to influence the legal implementation of the policy of empowering poor women through PKH in the Banyumas Regency Social and Permades Department. Supporting factors include the availability of PKH regulations; availability of cash and complementary assistance; availability of facilities in various PKH services and secretariats; good PKH activities; and there is synergy between Dinsospermades, District Coordinators, District Coordinators, Social Facilitators, and PKH recipients. Inhibiting factors include, insufficient number of Human Resources (HR); and lack of facilities at P2K2. Keywords : legal implementation, poverty, women’s empowerment, program keluarga harapan